Hambatan Belajar Potensial pada Penjumlahan dan Pengurangan Bilangan Cacah: Tinjauan Praxeology Buku Teks Matematika Sekolah Dasar - Mufarrahatus Syarifah; Nuris Hidayat (STKIP Singkawang, 2025)
This study aims to identify potential learning obstacles to the addition and substraction of whole numbers in mathematics textbook for grade 2 elementary school. Textbook analysis was carried out using a praxeological review. Task activities in the textbook are classified based on the praxeology components (type of task, technique, technology, and theory). Then, the content of the book is described based on the classification made to see potential learning obstacles that arise. Potential learning obstacles found are classified into didactic and epistemological. Didactic learning obstacle are indicated by the lack of sequential presentation of concepts and limited exploration of calculation techniques. Epistemological learning obstacle are indicated by the limited representation of the situation of the meaning of addition and subtraction of whole numbers.